Transforming Southeast Europe During the Long 19th Century : Persons and Personalities as Agents of Modernization in the Ottoman and Post-Ottoman Space - Antonova-Goleva, Boriana; Masheva, Ivelina (Balkan Studies Library, 2024)
The volume offers a new perspective towards the transformation of Southeast Europe through the lens of persons and personalities as agents of modernization. Exploring the experience of modernity through the lens of the personal allows for approaching transformation as a result of a specific conjuncture of ideas, influences, and beliefs. The book chapters address topics as diverse as political and institutional development, social and cultural transformations, economic and legal changes, and technological innovations in the Ottoman and Post-Ottoman Balkans. By doing so, the collection approaches the advent of modernity in Southeast Europe from various and even contrasting standpoints, highlighting the multiplicity of actors as well as the entanglement and interconnectedness of topics, arenas and scales of the modernization process.